Hair loss: a clinical update. (2nd November 2019) - Millar-Hume, Lucy; Ali, Farah
Abstract : Hair loss is classified into non-scarring and scarring alopecias, the latter being further subdivided into primary and secondary forms. These classifications are also referred to as non-cicatricial and cicatricial hair loss. This article focuses on androgenic alopecia (AGA) and will, at times, be referred to as male pattern hair loss (MPHL) or female pattern hair loss (FPHL). Essentially, AGA is a non-scarring, benign form of alopecia, generally related to ageing and where, on the whole, a proportion of hair can grow back. Aestheticians should be prepared to answer a patient's questions and concerns and be familiar with the current levels of evidence surrounding the myriad of treatments available.